1989
DOI: 10.1172/jci114134
|View full text |Cite
|
Sign up to set email alerts
|

Chronic blockade of endogenous atrial natriuretic polypeptide (ANP) by monoclonal antibody against ANP accelerates the development of hypertension in spontaneously hypertensive and deoxycorticosterone acetate-salt-hypertensive rats.

Abstract: To explain the pathophysiological significance of endogenous atrial natriuretic polypeptide (ANP) in the development of hypertension, we examined the effect of chronic, repetitive administrations of MAb raised against a-rat ANP in two rat models of hypertension, spontaneously hypertensive rats of the stroke prone substrain (SHR-SP), and deoxycorticosterone ac-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 41 publications
5
25
0
Order By: Relevance
“…23 In addition, we observed that intravenous injection of a 100 /xg dose of purified MAb KY-ANP-II inhibited the increase in plasma cyclic GMP induced by administration of exogenous ANP (20 /ig/kg i.v.) to the intact rat, 24 confirming the previous characterization of Itoh et al 21 The dose of MAb KY-ANP-II (0.55 fig) used in the current experiment is equivalent to the anti-ANP antibody contained in 0.55 jil of mouse ascites fluid. This is 0.5% of the peripheral intravenous dose (100 /il of ascites fluid) of this monoclonal antibody used in previous studies by Itoh et al 21 …”
Section: \\supporting
confidence: 89%
See 1 more Smart Citation
“…23 In addition, we observed that intravenous injection of a 100 /xg dose of purified MAb KY-ANP-II inhibited the increase in plasma cyclic GMP induced by administration of exogenous ANP (20 /ig/kg i.v.) to the intact rat, 24 confirming the previous characterization of Itoh et al 21 The dose of MAb KY-ANP-II (0.55 fig) used in the current experiment is equivalent to the anti-ANP antibody contained in 0.55 jil of mouse ascites fluid. This is 0.5% of the peripheral intravenous dose (100 /il of ascites fluid) of this monoclonal antibody used in previous studies by Itoh et al 21 …”
Section: \\supporting
confidence: 89%
“…MAb KY-ANP-II recognizes human ANF-(99-126) and rat ANF-(99-126) equally and blocks the ability of both exogenous and endogenous ANP to elevate plasma cyclic GMP levels. 21 Intravenous administration of MAb KY-ANP-II has been shown to produce significant reductions in plasma cyclic GMP levels in stroke-prone SHR (SHRSP) and deoxycorticosterone acetate-salt rats, indicating that the antibody can block the activity of rat ANF-(99-126) in the intact rat. We purified IgG containing MAb KY-ANP-II from mouse ascites fluid (1 ml) with a protein A agarose column.…”
Section: \\mentioning
confidence: 99%
“…Several lines of evidence support the concept that ANP activates particulate guanylate cyclase and increases cyclic GMP accumulation in numerous cell types and tissues, including the vascular smooth muscle, endothelial cells, fibroblasts, and renal cells [44]. In the human and rat, an intravenous administration of ANP has been reported to elevate the plasma cGMP level [16,18]. Together, these findings suggest the significance of cyclic GMP as a second messenger and biological marker of ANP.…”
Section: Discussionmentioning
confidence: 80%
“…Recently, evidence has suggested that cardiovascular homeostasis is determined by a balance in cross-talk between the natriuretic peptide system and the angiotensin system [22]. Several investigations of ANP in cardiac tissues have been performed in the hypertensive animal model, including the spontaneously hypertensive rat (SHR) [3,19,29,31], SHR-stroke prone [2,29], deoxycorticosterone acetate (DOCA)-salt rat [18,34], and the Dahl salt sensitive rat with sodium chloride-induced hypertension [39]. To our knowledge, no data have been published on the plasma and heart ANP levels of THM in relation to hypertension by RAS.…”
Section: Introductionmentioning
confidence: 99%
“…A third natriuretic peptide receptor with no intracellular guanylyl cyclase domain, dubbed the clearance receptor (C-receptor), is thought to be engaged in the receptor-mediated degradation of natriuretic peptides [2]. The ANP, BNP/GC-A system plays a pivotal role in the regulation of cardiovascular homeostasis, as demonstrated by their augmentation in various pathophysiological states such as heart failure [4][5][6][7][8], myocardial infarction [9, 10], cardiac hypertrophy [11,12], and hypertension [13][14][15]. In fact, ANP and BNP are cardiac hormones secreted primarily by the atrium and ventricle of the heart, respectively [8,15], with strong diuretic, natriuretic, and vasodilatory activities [4, 5, 8].…”
mentioning
confidence: 99%